BPJS PATIENT SATISFACTION WITH BPJS REFERRAL SERVICES AT KIMIA FARMA PHARMACY 591 ZAMRUD EAST BEKASI - Rahmat Widiyanto; M. Fathan Nugrah Utama; Niko Prasetya; Erni Hernawati (Jurnal Kesehatan Farmasi, 2025)
Background: Pharmaceutical services have undergone changes, that was initially focused on drug management (drug-oriented) to comprehensive services that include medication management and clinical pharmacy services aimed at improving patients' quality of life. As one of the flagship programs to improve the quality of services for BPJS Health participants and facilitate access to healthcare for patients with stable chronic conditions who still require long-term medication or nursing care, the implementation of the Back Referral Program (PRB) has been optimized. This study aims to determine the satisfaction level of BPJS participants with the BPJS back referral service at Kimia Farma Pharmacy 591 Zamrud, as assessed through five dimensions: reliability, responsiveness, assurance, empathy, and tangibles. Method: This study employed a non-experimental method with a quantitative descriptive design. The sample consisted of 143 respondents selected using purposive sampling. The research instrument was a questionnaire that had been validated and tested for reliability. Results: The results of the study indicate that the dimensions of reliability, responsiveness, empathy, and tangibles obtained fairly good average scores, ranging from 3.97 to 3.98, while the assurance dimension showed the lowest score, at 3.20. The assessment of the five dimensions of respondent satisfaction was mostly at the satisfied level, with 117 respondents (81.82%), followed by very satisfied with 15 respondents (10.49%), fairly satisfied with 11 respondents (7.69%), and none who stated they were dissatisfied or very dissatisfied. Conclusion: Based on the research results, it can be concluded that BPJS back referred patients are satisfied with the services at Kimia Farma Pharmacy 591 Zamrud Bekasi Timur.